In-vitro antimalarial activities of withania somnifera, gymnema sylvestre, ocimum gratisimum and cajanus cajan (2010)
A study was carried out to determine the efficacy of four plants, Withania somnifera (WS), Gymnema sylvestre (GS), Ocimum gratisimum (OG) and Cajanus cajan (CC) traditionally used in the treatment of malaria in Nigeria and India. Ethanolic extracts of these plants were tested in vitro on choloroquine sensitive (MRC-pf-2) and resistant (MRC-pf-303) strains of Plasmodium falciparum for their anti-malarial activity. The IC(50) values of these plants were calculated and found to be OG (IC(50) = 23.48 µg/ ml), WS (IC(50)= 45.24 µg/ ml), GS (IC(50) = 45.25 µg/ ml) for the pf sensitive strain and CC (IC(50) = 47.52 µg/ ml) in the pf resistant strain. Others, GS IC(50) = 69.70 µg/ ml (resistant strain), CC IC(50) = 72.3lµg/ ml (sensitive strain), WS IC(50)= 88.30 µg/ ml (resistant strain), OG IC(50)= 121.76µg/ ml (resistant strain). Higher concentrations caused total inhibition of the parasite at the ring stage. Ocimum gratisimum showed the most significant antimalarial effect on the parasites sensitive strain. Results lend some credence to the use of medicinal plants in the treatment of malaria and the need to study the active constituents of effective ones.